Latin Monetary Union and Scandinavian Monetary Union – similarities and differences - Sawa, Dawid (Koszty współczesnych kryzysów, 2021)
The article describes the creation of the Latin Monetary Union and Scandinavian Monetary Union as well as the attempts to unify the countries of the European continent for economic purposes. The article describes the creation of the Latin Monetary Union and the Scandinavian Monetary Union as well as the attempts to unify the countries of the European continent for economic purposes. In this concept, politics plays an important role as it also sets directions for the economy. Politics takes a central place in shaping reality, which is why its role in the following chapter is so important. The article deals with the matter of bimetalism, which plays an important role in the concept of monetary unions. The above – mentioned organization no longer exist and their functioning was characterized by both similarities and differences, as will be presented. In the text, the author will use comparative and historical method, while analyzing documents that are to bring the above matter closer to the reader.